The British Labour Party and Palestine 1917-1949 - Sargent, Andrew (1980)
The thesis is an attempt to examine the Labour Party's involvement with the question of Palestine from the time of the party's first declaration on the subject in 1917 to the de facto recognition by a Labour Government of the State of Israel in January 1949.